2010
DOI: 10.1016/j.brainres.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos induction by a 14T magnetic field in visceral and vestibular relays of the female rat brainstem is modulated by estradiol

Abstract: There is increasing evidence that high magnetic fields interact with the vestibular system of humans and rodents. In rats, exposure to high magnetic fields of 7T or above induces locomotor circling and leads to a conditioned taste aversion if paired with a novel taste. Sex differences in the behavioral responses to magnetic field exposure have been found, such that female rats show more locomotor circling and enhanced conditioned taste aversion compared to male rats. To determine if estrogen modulates the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
2
8
1
Order By: Relevance
“…Also consistent with earlier findings (3,28), magnetic field exposure induced c-Fos in visceral relays of the brain stem. The induction by magnetic field exposure at 0°and 180°was significantly greater than the c-Fos induced by restraint stress alone in the sham controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also consistent with earlier findings (3,28), magnetic field exposure induced c-Fos in visceral relays of the brain stem. The induction by magnetic field exposure at 0°and 180°was significantly greater than the c-Fos induced by restraint stress alone in the sham controls.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, exposure at 0°induced more c-Fos in the left vestibular nuclei, whereas exposure at 180°i nduced significantly more c-Fos in the right vestibular nuclei. Previously, we have reported some asymmetrical c-Fos induction after 30-min head-up exposure to 14.1 T in ovariectomized female rats (with modulation by estrogen replacement), although the lateralization was not as robust as observed here in mice (3).…”
Section: Discussioncontrasting
confidence: 73%
“…In fact, as estrogen upregulates P receptors (24), this mechanism is likely involved with the respiratory effects of P. E 2 and P receptors (ER-␣, ER-␤; PR-A, PR-B) were identified in many respiratory regions of the brain, including the nucleus of the solitary tract (38,39), the hypoglossal nuclei (4), and the motor nuclei of the phrenic nerve (4). In fact, some studies have reported an inhibitory effect of E 2 in some areas important for V E (10,44,46,49). Also, studies in OVX rats (8) and castrated cats (20,21) have demonstrated that administration of P combined with estrogen promotes an increase in pulmonary V E and hypercapnic ventilatory response through receptor-mediated mechanisms of action involving central and peripheral sites.…”
Section: Ovariectomy Hormonal Replacement V E Metabolism and Tbmentioning
confidence: 99%
“…Exposure to magnetic fields at 7T or above can serve as the unconditioned stimulus for conditioned taste aversion or avoidance (CTA) learning, suggesting that exposure has an aversive component [14, 15, 17]. Consistent with stimulation of the vestibular system, magnetic field exposure induces c-Fos in vestibular and visceral relays of the rat brainstem [18, 19]. The effects of the high magnetic field on locomotion and CTA are maximal after head exposure [20].…”
Section: Introductionmentioning
confidence: 99%